Implementation of Agile Methods in the Development of a Mobile-based Hybrid Learning Management System Application - Wiliramayanti Wiliramayanti; Hoiriyah Hoiriyah; Moh. Aminollah Hamzah; Rofiuddin Rofiuddin (SISTEMASI, 2026)
The rapid advancement of digital technology in higher education has increased the demand for learning systems that not only support academic activities but are also easily accessible through smartphones, the devices most frequently used by university students. Although Learning Management Systems (LMSs) have been widely adopted, most existing implementations remain web-based, limiting the optimization of mobile learning experiences. This study aims to develop a mobile-based Hybrid Learning Management System (HyLMS) that integrates synchronous and asynchronous learning within a single platform. The system was developed using the Agile Development methodology to facilitate iterative development and continuous adaptation to user requirements. The development process consisted of requirements gathering, system design, implementation, testing, and evaluation. The resulting application provides essential features, including user registration, authentication, course management, learning material access, assignment submission, discussion forums, notifications, and assessment. Black Box Testing confirmed that all system functionalities operated as expected. Furthermore, user experience was evaluated using the User Experience Questionnaire (UEQ) involving 35 respondents, with positive results across all evaluation dimensions. The highest score was achieved in the Stimulation dimension (1.52), indicating a high level of user engagement and motivation. These findings demonstrate that the proposed mobile-based HyLMS effectively supports hybrid learning by providing a more flexible, integrated, and user-centered learning environment for higher education institutions.